Risk assessment for epithelial ovarian cancer: Proposing a new approach to a deadly problem. (August 2014) - Chu, Mary M.; Fishman, David
Abstract: Presently the majority of women diagnosed with epithelial ovarian cancer (EOC) have advanced stage disease (III–IV) with a poor 5-year survival rate (12–30 %). This significantly contrasts when early stage disease is detected, which has a 5-year survival rate approximating 90 %. Therefore, detection of early stage disease is critical to making an impact on outcome. By using genetic algorithms, modifications of transvaginal ultrasonography and use of novel biomarkers, we propose a risk assessment profile to identify at-risk women and enable ovarian cancer screening to become a reality. Such a novel algorithm starts by applying classic genetic pedigree assessment and uses a panel of multiple biomarkers that identify both phenotypic and genotypic expression of high-risk markers followed with conventional ultrasound and advanced ultrasound techniques such as microvascular contrast-enhancement as a secondary test. We presently employ a multidisciplinary program incorporating genetics, molecular biology, tumor immunology, gynecologic oncology and diagnostic imaging to identify asymptomatic high risk women.